Determination of ultra-trace levels of cobalt in water and wheat flour samples using cloud point extraction coupled with laser thermal lens spectrometry. Issue 6 (25th January 2018) - Han, Quan; Huo, Yanyan; Yang, Xiaohui; He, Yaping; Wu, Jiangyan; Cai, Hongli
Abstract : A highly sensitive method for the determination of ultra-trace levels of cobalt using cloud point extraction (CPE) coupled with thermal lens spectrometry was proposed. Abstract : A highly sensitive method for the determination of ultra-trace levels of cobalt using cloud point extraction (CPE) coupled with thermal lens spectrometry was proposed. It is based on the complexation of cobalt with a suitable chelating agent, 2-(5-iodio-2-pyridylazo)-5-dimethylaminoaniline (5-I-PADMA), and subsequent micelle-mediated extraction of the product using non-ionic surfactant octylphenoxypolyethoxyethanol (Triton X-114) as an extracting agent. The effects of experimental conditions such as pH, concentration of 5-I-PADMA and Triton X-114, equilibration temperature and time on CPE were studied. After phase separation, the surfactant rich phase containing the complex was dissolved with HCl–acetone solution prior to its analysis by thermal lens spectrometry. A single mode He–Ne laser with λ = 632.8 nm was used to produce both excitation and probe beams. Under optimal conditions, the calibration plot was linear in the range of 0.2–6.0 ng mL −1 cobalt, with a correlation coefficient of 0.9975. The detection limit obtained under optimum conditions was 0.02 ng mL −1 . The sensitivity was enhanced by 331 times compared to that of the conventional spectrophotometric method. The proposed method was successfully applied to the extraction and determination of cobalt in water and wheat flour samples.